Conservation and Diversification of Circadian Rhythmicity Between a Model Crassulacean Acid Metabolism Plant Kalanchoë fedtschenkoi and a Model C3 Photosynthesis Plant Arabidopsis thaliana - Moseley, Robert C.; Mewalal, Ritesh; Motta, Francis; Tuskan, Gerald A.; Haase, Steve; Yang, Xiaohan (Frontiers in Plant Science, 2018)
Crassulacean acid metabolism (CAM) improves photosynthetic efficiency under limited water availability relative to C3 photosynthesis. It is widely accepted that CAM plants have evolved from C3 plants and it is hypothesized that CAM is under the control of the internal circadian clock. However, the role that the circadian clock plays in the evolution of CAM is not well understood. To identify the molecular basis of circadian control over CAM evolution, rhythmic gene sets were identified in a CAM model plant species (Kalanchoë fedtschenkoi) and a C3 model plant species (Arabidopsis thaliana) through analysis of diel time-course gene expression data using multiple periodicity detection algorithms. Based on protein sequences, ortholog groups were constructed containing genes from each of these two species. The ortholog groups were categorized into five gene sets based on conservation and diversification of rhythmic gene expression. Interestingly, minimal functional overlap was observed when comparing the rhythmic gene sets of each species. Specifcally, metabolic processes were enriched in the gene set under circadian control in K. fedtschenkoi and numerous genes were found to have retained or gained rhythmic expression in K. fedtsechenkoi. Additonally, several rhythmic orthologs, including CAM-related orthologs, displayed phase shifts between species. Results of this analysis point to several mechanisms by which the circadian clock plays a role in the evolution of CAM. These genes provide a set of testable hypotheses for future experiments.